Coping strategies adopted by women victims of violence [Estratégias de enfrentamento adotadas por mulheres vítimas de violência] [Estrategias de enfrentamiento adoptadas por mujeres víctimas de violencia] - Laís Costa; Rayane Gonçalves Lordes; Dherik Fraga; Nathália Miguel Teixeira Santana; Susana Bubach; Franciéle Marabotti Costa Leite (Revista Enfermagem UERJ, 2018)
Objective: to examine the coping strategies adopted by women victims of violence. Method: in this quanti-qualitative, descriptive study of 19 women victims of violence, who attended the Multidisciplinary Support Center in Serra, Espírito Santo, in 2013, semi-structured interview and recording were used to collect socioeconomic and violence data. Content analysis was applied to the testimonies. The study was approved by the research ethics committee. Results: the women were predominantly aged 39 years or less, had completed secondary education, had their own income, a family income of 1 to 2 minimum wages, and were Evangelicals. The themes recovered from their accounts were: combating violence by focusing on the problem (42.1%), combating violence by focusing on emotion (26.3%), combating violence by focusing on emotion and religion (21.1%), and combating violence by focusing on emotion and the problem (10.5%). Conclusion: women in situations of violence experienced different manners of coping with this disorder, by focusing on the problem, emotion and religion.